Finalizing the application of analytical procedures in The audit of financial statements conducted by aasc ltd,. - Tuong, Dieu Anh (2020)
The objective of this study was to investigate the application of analytical procedure in audit process of AASC Limited Liability Company, one of top Vietnamese audit firms, which might partly answer for the question: “Is analytical procedure not applied thoroughly and efficiently?” There are two purposes focused on in the thesis which are getting deep understanding of analytical procedures in auditing administration expense and receivables accounts and giving some comments based on the theoretical frameworks.